PENGARUH MANAJAMEN AGRIBISNIS TERHADAP PRODUKTIVITAS PETANI KOPI PETIK MERAH DI DESA BANDUNG JAYA KECAMATAN KABAWETAN KABUPATEN KEPAHIANG - Darwan Effendi; Dodi Aprianto; Tesi Rahma (Jurnal Riset Rumpun Ilmu Tanaman, 2022)
Indonesia is one of the countries known for its abundant agricultural products, agricultural products in Indonesia are very diverse, ranging from horticultural crops, spices, fruits and plantation crops. These agricultural products are spread throughout Indonesia. Kepahiang is located in the highlands of Bukit Barisan which is one of the districts in Bengkulu Province. The area of ​​Kepahiang Regency reaches approximately 710,110 hectares or 710.11 square kilometers (Kepahiang Regency Statistics Center, 2021), geographically Kepahiang Regency is located in the highlands with a cool climate. The agricultural sector plays an important role in the economy of Kepahiang Regency because it is the main sector that provides the largest role in the formation of the Gross Regional Domestic Product (GRDP). This research was conducted with the aim of knowing whether there is a positive and significant influence of agribusiness management on the productivity of red-picked coffee farmers in Bandung Jaya Village, Kabawetan District, Kepahiang Regency. There are two variables in this study, namely the independent variable is agribusiness management and the dependent variable is farmer productivity. The research population was red-picked coffee farmers in the village of Bandung Jaya who were members of a black civet farmer group, totaling 12 people. Data collection techniques used questionnaires and documentation. Data analysis techniques used simple linear regression questionnaires and tested the validity and reliability of the data. Based on the research that has been carried out, the results obtained are simple linear regression with the equation Y = 14.538 + 0.646 X and based on the validity test all statement items are said to be valid because (X) r count > r table (0.5760) and all statement items are said to be reliable because the value con'bach alpha > 0.60. Based on the calculations obtained, it is known that the agribusiness management variable has a significant positive effect on increasing the productivity of potato farmers and the results of the hypothesis can be accepted.